2016
DOI: 10.21640/ns.v8i17.544
|View full text |Cite
|
Sign up to set email alerts
|

Promoción del crecimiento en plantas de Capsicum annuum por nanopartículas de óxido de zinc

Abstract: Las aplicaciones de la nanotecnología (NT) en los sistemas agrícolas son diversas, ofreciendo el potencial para mejorar significativamente su productividad y eficiencia al reducir costos y cantidades de agroquímicos aplicados. Las nanopartículas (NPs) metálicas de óxido de zinc, cobre y fierro, ya sean puras o mezcladas con plata, están siendo estudiadas globalmente por su potencial agrícola como promotores de crecimiento, nanofertilizantes y antimicrobiales. Considerando lo antes señalado, el objetivo de este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
1
7
0
2
Order By: Relevance
“…Zinc oxide nanoparticles (ZnO NPs) in agriculture have potential in promoting seed germination rate [23,24], plant growth and development [25][26][27][28], as well as fungicide and bactericide properties [28][29][30][31]. However, phytotoxic effects have also been attributed to it, particularly inhibiting root growth [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc oxide nanoparticles (ZnO NPs) in agriculture have potential in promoting seed germination rate [23,24], plant growth and development [25][26][27][28], as well as fungicide and bactericide properties [28][29][30][31]. However, phytotoxic effects have also been attributed to it, particularly inhibiting root growth [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…It acts as a precursor of phytohormones such as auxins, which promote cell elongation and division and have an influence on the reactivity of indoleacetic acid, and as a hormonal phytostimulant, associated with the biosynthesis of cytokinins and gibberellins. In addition, it is essential for photosynthesis and facilitates carbohydrate metabolism in plants because Zn stabilizes or activates the proteins involved in these processes [30,[44][45][46], increases biological fitness, and helps plants to cope with stress conditions [20].…”
Section: Introductionmentioning
confidence: 99%
“…The promoter effect could be related to the zinc role as a precursor in the synthesis of auxins that promote cell division, as well as its influence on the reactivity of indoleacetic acid, which functions as a hormonal phytostimulant [ 8 , 13 , 17 , 18 ]. Furthermore, it is possible that ZnO nanoparticles could be involved in a greater production of the phytohormones cytokine and gibberellin, apart from inducing the activity of antioxidant enzymes [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Samreen et al [36], while evaluating the effect of zinc application on rate of growth as well as on chlorophyll and protein, concluded that applying 2 µM to the nutritious solution improved the plant Zinc is considered to be one of the eight essential micronutrients for plants. It is necessary in small amounts and crucial for appropriate development [7], since it promotes an increase in biomass and enzymatic action. Moreover, it stabilizes chlorophyll molecules and regulates gene expression [8,9].…”
Section: Content Of Photosynthetic Pigmentsmentioning
confidence: 99%
“…Zinc is considered to be one of the eight essential micronutrients for plants. It is necessary in small amounts and is crucial for appropriate development [7], since it promotes an increase in biomass and enzymatic action. Moreover, it stabilizes chlorophyll molecules and regulates gene expression [8,9].…”
Section: Introductionmentioning
confidence: 99%